2009
DOI: 10.1007/s11664-009-0950-9
|View full text |Cite
|
Sign up to set email alerts
|

Interfacial Reactions Between Sn-Zn Alloys and Ni Substrates

Abstract: Interfacial reactions between Sn-Zn alloys and Ni substrates after annealing at 463 K have been studied. Only one intermetallic compound (IMC), c-Ni 5 Zn 21 , was observed at the Sn-Zn/Ni interfaces, although other IMC(s) in the Ni-Sn and Ni-Zn system can stably exist at this temperature. Taking into account nucleation along with diffusion kinetics, formation of the reaction product has been reasonably modeled. In addition, growth kinetics for the reaction layer has been quantified. The results indicate that t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(9 citation statements)
references
References 31 publications
0
9
0
Order By: Relevance
“…Chan et al [10] reported that Ni 5 Zn 21 growth is diffusion-controlled at the liquid/solid Sn-9wt%Zn/Ni interface at temperatures ranging from 250 C to 350 C for 1 h to 4 h. Yen et al [14] studied the interfacial reactions of Sn-9wt%Zn with Au/Ni(1.6 mm)/SUS304 at 240 Ce270 C. They also observed that the interfacial reactions are governed by diffusion mechanism. Zhu et al [15] studied the solid/ solid interfacial reactions between Ni and SneZn solders (Sn-8at% Zn, Sn-35at%Zn and Sn-60at%Zn) at 190 C for various durations from 480 h to 1200 h. Similarly, the Ni 5 Zn 21 growth results implied that the mechanism is diffusion-controlled. Additionally, they reported that the growth rate increases with increasing Zn contents.…”
Section: Introductionmentioning
confidence: 99%
“…Chan et al [10] reported that Ni 5 Zn 21 growth is diffusion-controlled at the liquid/solid Sn-9wt%Zn/Ni interface at temperatures ranging from 250 C to 350 C for 1 h to 4 h. Yen et al [14] studied the interfacial reactions of Sn-9wt%Zn with Au/Ni(1.6 mm)/SUS304 at 240 Ce270 C. They also observed that the interfacial reactions are governed by diffusion mechanism. Zhu et al [15] studied the solid/ solid interfacial reactions between Ni and SneZn solders (Sn-8at% Zn, Sn-35at%Zn and Sn-60at%Zn) at 190 C for various durations from 480 h to 1200 h. Similarly, the Ni 5 Zn 21 growth results implied that the mechanism is diffusion-controlled. Additionally, they reported that the growth rate increases with increasing Zn contents.…”
Section: Introductionmentioning
confidence: 99%
“…2 Taking into account that Zn has a strong chemical affinity with Cu, the amount of soluble Zn content in the solder should be reduced. [18][19][20] Similar behavior for Sn-Zn with Ga and Na 22 on Cu substrate was observed. The addition of 0.5 (wt.%) Ga to eutectic Sn-Zn caused a reduction in the IMC layer at the interface.…”
Section: Introductionmentioning
confidence: 60%
“…Their compositions were both determined to be Zn-19.5 at %Ni without detectable In or Sn, and they are presumed to be the Ni 5 Zn 21 phase according to the NieZn binary phase diagram [33]. The reaction product, Ni 5 Zn 21 , is the same as that formed in the solid/solid SneZn/Ni reactions with the Zn content higher than 2 wt.% [34,35]. However, an additional (Ni,Zn) 3 Sn 4 phase has been found in SneZn/Ni reactions at 170 C when the Zn content is lower than 1 wt.% [35].…”
Section: Resultsmentioning
confidence: 99%